Toward exercise as medicine for adolescents with bipolar disorder (TEAM-BD): A feasibility study. (March 2022) - Khoubaeva, Diana; Popel, Najla; Kcomt, Andrew; MacIntosh, Bradley; McCrindle, Brian; Omrin, Danielle; Michalak, Erin; Faulkner, Guy; Roane, Jessica; Fiksenbaum, Lisa M.; Mitchell, Rachel H.B.; Shickh, Randa; et al.
Abstract: Objectives: Bipolar disorder (BD) is associated with decreased cardiorespiratory fitness (CRF) and exercise. Despite the potential benefits for physical and mental health, there is a gap in knowledge regarding treatments targeting improved CRF for BD. This treatment development and feasibility study sought to bridge the knowledge-to-action gap in this area. Methods: Twenty youth with BD, 18.0 ± 2.3 years old, enrolled in an exercise behavior change counselling (BCC) intervention targeting improved CRF. The 12-week active intervention included four in-person sessions, augmented by phone/texting sessions on intervening weeks. Optional modules included exercise coaching, family involvement, and peer support. Booster phone/texting sessions occurred at weeks 16 and 20. Participants completed CRF testing at weeks 0, 2, 8, 12, and 24. Results: Seventy percent of participants (14/20) completed all study visits and measures. In the overall enrolled sample, 82% of CRF tests were completed (range 0–5 of 5). There were no significant changes in subjective (via self-report) and objective (via Fitbit) measures of physical activity or in CRF, though CRF testing was consistently associated with acute post-exercise improvement in mood. Most participants reported being very satisfied with the intervention following the 12-week active intervention (13/14) and at week 24 (12/14). Therapist fidelity to the BCC manual was high. Conclusion: Good attendance and study adherence provides preliminary evidence of the feasibility and acceptability of a behavioral intervention targeting CRF in youth with BD. Future studies refining the current intervention are warranted toward a goal of demonstrating improved CRF in a randomized controlled trial. Highlights: A multidisciplinary team developed a behavior change intervention for increasing cardiorespiratory fitness in youth with BD. Twenty youth with BD were recruited and 14 completed the full 24-week intervention. Among participants retained to week 24, study measure completion rate and overall satisfaction were high. There were no significant changes in cardiorespiratory fitness after the active 12-week intervention and week 24 follow-up. Cardiorespiratory fitness testing was consistently associated with acute post-exercise improvement in mood.